Method for improving mechanical property of carbon paper for proton exchange membrane fuel cell

Through the combination of modified carbon fiber and chopped aramid fiber and hot pressing treatment of phenolic resin, the problem of insufficient mechanical properties of carbon paper for proton exchange membrane fuel cells is solved, significantly improving the bending strength and interface bonding strength of carbon paper, and improving the Mechanical properties of carbon paper.

CN119243507APending Publication Date: 2025-01-03ZHEJIANG UNIV OF SCI & TECH

Patent Information

Application Number
CN202411387639.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-06
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing technology cannot effectively improve the mechanical properties of carbon paper for proton exchange membrane fuel cells. Although it can improve the electrochemical performance and power generation power of fuel cells, there is still room for improvement in the mechanical properties of finished carbon paper products.

Method used

By combining modified carbon fiber and chopped aramid fiber, specific chemical treatment and hot pressing processes include the addition of Tis-HC1 solution and dopamine hydrochloride solution in carbon fiber and aramid fibers, followed by impregnation and heat in phenolic resin Pressure treatment and finally carbonized in a tube furnace to improve the mechanical properties of carbon paper.

Benefits of technology

It significantly improves the bending strength and interface bonding strength of carbon paper, enhances the mechanical properties of the material, improves the communication pores and impregnation capabilities of carbon paper base paper, and improves the mechanical properties of carbon paper.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243507A_ABST
    Figure CN119243507A_ABST
Patent Text Reader

Abstract

The invention discloses a method for improving the mechanical property of carbon paper for a proton exchange membrane fuel cell, which comprises the following steps: obtaining carbon paper raw paper by a carbon fiber modification method and a carbon paper preparation method, and carrying out hot pressing and carbonization on the carbon paper raw paper to obtain a carbon paper finished product. The surface of a finished product can be in an uneven state, the interface bonding strength of the material is effectively improved, the number of communicating pores of the carbon paper body paper is increased, the follow-up phenolic resin dipping capacity of the body paper is improved, and therefore the mechanical properties such as the bending strength of the carbon paper body paper are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of carbon paper, and in particular to a method for improving the mechanical properties of carbon paper for proton exchange membrane fuel cells. Background Art

[0002] Hybrid fiber reinforced resin matrix composites are made by embedding two or more fibers into a resin matrix, combining the advantages of several fiber reinforced composite materials. Compared with traditional resin matrix composites, hybrid fiber reinforced composites have better mechanical properties and have been used in many fields such as aviation and automobiles. This type of composite material can meet the requirements of quality, strength, impact resistance, cost, etc. through optimized design, such as changing fiber type, fiber angle, fiber volume fraction, hybrid configuration and hybrid method.

[0003] The Chinese invention patent with publication number CN118412482A discloses a method for preparing a microporous layer of a proton exchange membrane fuel cell with a composite conductive component. The invention patent and this case are developed by the same research and development team. The principle of improving the performance of the invention patent is to add a polymer conductive material into the microporous layer to improve the conductivity and hydrophilicity, improve the water management ability, surface flatness and electrochemical performance of the microporous layer, and thus improve the performance of the gas diffusion layer of the fuel cell. However, although this technical solution can improve the performance of the gas diffusion layer of the fuel cell, reduce the concentration polarization of the battery, and improve the power generation and electrochemical performance of the battery, it cannot effectively improve the mechanical properties of the finished carbon paper. Therefore, how to develop a method that can improve the mechanical properties of carbon paper for proton exchange membrane fuel cells based on existing technical research and development results has become a problem that needs to be solved urgently. Summary of the invention

[0004] The object of the present invention is to provide a method for improving the mechanical properties of carbon paper for proton exchange membrane fuel cells.

[0005] The technical solution of the present invention is a method for improving the mechanical properties of carbon paper for proton exchange membrane fuel cells, comprising the following steps:

[0006] Modified carbon fiber method:

[0007] Step 1, select carbon fiber with a length of 1-15 mm and disperse it into 0.5-3 mol / L NaOH solution, stir and let stand to remove grease impurities on the surface of the carbon fiber;

[0008] Step 2: Prepare 0.005-0.5 mol / L Tis-HCl solution, add a few drops of Tis-HCl solution to the solution in step 1 to adjust the pH value to 8-9, add the solution after pH adjustment to dopamine hydrochloride solution to prepare 2-3 g / L reaction solution, stir and react at room temperature, the color of the solution changes from colorless and transparent to light red, then to dark red, and finally to dark black, and the stirring ends; filter, wash, and dry in an oven at 50-80°C to obtain modified carbon fiber;

[0009] Carbon paper preparation method:

[0010] The short-cut aramid fiber is added into 5-15 ml of polyethylene oxide and 1-3 L of tap water to make the mass fraction of the short-cut aramid fiber reach 2%-14%, and then the solution is placed in a deagglomerator for deagglomeration for 5-15 minutes to completely deagglomerate the short-cut aramid fiber to obtain a short-cut aramid fiber solution; then 1.1-1.5 g of modified carbon fiber with a diameter of 3-5 mm and 0.1-0.2 g of polyvinyl alcohol fiber with a diameter of 3-10 mm are added to make the modified carbon fiber, polyvinyl alcohol fiber and short-cut aramid fiber solution fully deagglomerated. The carbon paper base paper is prepared by mixing the raw materials and the raw materials evenly to obtain a slurry, and then the slurry suspension is poured into a paper sheet former, and the bubbles are homogenized for 1-5 minutes to make the fibers evenly dispersed; the water valve is opened to allow the fibers to freely settle on the copper mesh to form a carbon paper base paper wet paper web, and absorbent paper is used to absorb excess water in the wet paper web, and finally the wet paper web is placed on a flat vulcanizer, and hot pressed for 10-20 minutes under the conditions of 100-250° C. and 0.5-5 MPa to obtain a carbon paper base paper; and the carbon paper base paper is hot pressed and carbonized to obtain a carbon paper finished product.

[0011] In the above method for improving the mechanical properties of carbon paper for proton exchange membrane fuel cells, the step of hot pressing the carbon paper base paper is:

[0012] 5-15 g of phenolic resin is weighed and added with 50-150 g of anhydrous ethanol to prepare a 5-15% PF impregnation solution, and ultrasonic vibration is performed for 10-30 minutes to fully mix the phenolic resin impregnation solution, and the carbon paper base paper is ultrasonically impregnated in the phenolic resin impregnation solution for 5-20 minutes, and then placed in a blast drying oven at 50-100° C. for 40-80 minutes to pre-cure the phenolic resin at low temperature. After drying, it is hot-pressed using a flat vulcanizer at a hot pressing temperature of 100-200° C., a hot pressing strength of 1-5 MPa, and a hot pressing time of 20-80 minutes to obtain hot-pressed carbon paper.

[0013] In the aforementioned method for improving the mechanical properties of carbon paper for proton exchange membrane fuel cells, the steps of carbonizing the hot pressed carbon paper to obtain the finished carbon paper are:

[0014] The hot pressed carbon paper is placed in a tubular furnace, and high-purity nitrogen is introduced for 80-100 minutes. Then, the temperature is increased to 100-250°C at a heating rate of 3-10°C / min, and then increased to 800-1500°C at a heating rate of 5-15°C / min, and kept warm for 30-80 minutes. After the reaction is completed, the furnace body is cooled to room temperature to obtain a finished carbon paper product.

[0015] In the aforementioned method for improving the mechanical properties of carbon paper for proton exchange membrane fuel cells, the specific method for modifying carbon fibers is:

[0016] Step 1, select carbon fiber with a length of 4 mm and disperse it into 1 mol / L, stir it and let it stand to remove grease impurities on the surface of the carbon fiber;

[0017] Step 2: Prepare 0.01 mol / L Tis-HCl solution, add a few drops of Tis-HCl solution to the solution in step 1 to adjust the pH value to 8.5, add the solution after pH adjustment to dopamine hydrochloride solution to prepare 2.5 g / L reaction solution, stir the reaction at room temperature, the color of the solution changes from colorless and transparent to light red, then to dark red, and finally to dark black, and the stirring ends; filter, wash, and dry in an oven at 60°C to obtain modified carbon fiber.

[0018] In the aforementioned method for improving the mechanical properties of carbon paper for proton exchange membrane fuel cells, the specific preparation method of carbon paper is:

[0019] The short-cut aramid fiber is added into 10 ml of polyethylene oxide and 2 L of tap water so that the mass fraction of the short-cut aramid fiber reaches 8%, and then the solution is placed in a deflaker for deflaking for 10 minutes to completely deflake the short-cut aramid fiber to obtain a short-cut aramid fiber solution; then 1.35 g of modified carbon fiber with a length of 4 mm and 0.15 g of polyvinyl alcohol fiber with a length of 6 mm are added to fully mix the modified carbon fiber, polyvinyl alcohol fiber and the short-cut aramid fiber solution to obtain a slurry, and then the slurry suspension is poured into a paper sheet former, and the bubble is homogenized for 3 minutes to uniformly disperse the fibers; the water valve is opened to allow the fibers to freely settle on a copper mesh to form a carbon paper base paper wet paper web, and absorbent paper is used to absorb excess water in the wet paper web, and finally the wet paper web is placed on a flat vulcanizer, and hot pressed for 15 minutes under the conditions of 150° C. and 1 MPa to obtain a carbon paper base paper; and the carbon paper base paper is hot pressed and carbonized to obtain a carbon paper finished product.

[0020] In the aforementioned method for improving the mechanical properties of carbon paper for proton exchange membrane fuel cells, the specific steps of hot pressing the carbon paper base paper are:

[0021] Weigh 10g of phenolic resin and add 90g of anhydrous ethanol to prepare a 10% PF impregnation solution. Ultrasonic oscillation is performed for 20 minutes to fully mix the phenolic resin impregnation solution. After ultrasonic impregnation of the carbon paper base paper in the phenolic resin impregnation solution for 10 minutes, it is placed in a blast drying oven at 80°C for 60 minutes to pre-cure the phenolic resin at low temperature. After drying, it is hot-pressed using a flat vulcanizer at a hot pressing temperature of 150°C, a hot pressing strength of 3MPa, and a hot pressing time of 60 minutes to obtain hot-pressed carbon paper.

[0022] In the aforementioned method for improving the mechanical properties of carbon paper for proton exchange membrane fuel cells, the specific steps of carbonizing the hot pressed carbon paper to obtain the carbon paper product are:

[0023] The hot pressed carbon paper was placed in a tubular furnace, purged with high-purity nitrogen for 90 minutes, then heated to 200°C at a heating rate of 5°C / min, then heated to 1100°C at a heating rate of 10°C / min, and kept warm for 60 minutes. After the reaction was completed, the furnace was cooled to room temperature to obtain the finished carbon paper.

[0024] Compared with the prior art, the present invention can make the surface appear uneven, effectively improve the interface bonding strength of the material, increase the interconnected pores of the carbon paper base paper, and help improve the subsequent ability of the base paper to be impregnated with phenolic resin, thereby improving the mechanical properties of the carbon paper base paper such as bending strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a scanning electron microscope image of the carbon paper in Example 2-4. DETAILED DESCRIPTION

[0026] The present invention is further described below in conjunction with the accompanying drawings and embodiments, but they are not intended to limit the present invention.

[0027] Example 1: A method for improving the mechanical properties of carbon paper for proton exchange membrane fuel cells. The experimental raw materials and reagents are as follows:

[0028] Experimental materials and reagents

[0029]

[0030]

[0031] The experimental instruments and equipment are as follows:

[0032]

[0033] The method of using carbon paper for proton exchange membrane fuel cells is as follows:

[0034] The steps include:

[0035] Modified carbon fiber method:

[0036] Step 1, select carbon fiber with a length of 1-15 mm and disperse it into 0.5-3 mol / L NaOH solution, stir and let stand to remove grease impurities on the surface of the carbon fiber;

[0037] Step 2: Prepare 0.005-0.5 mol / L Tis-HCl solution, add a few drops of Tis-HCl solution to the solution in step 1 to adjust the pH value to 8-9, add the solution after pH adjustment to dopamine hydrochloride solution to prepare 2-3 g / L reaction solution, stir and react at room temperature, the color of the solution changes from colorless and transparent to light red, then to dark red, and finally to dark black, and the stirring ends; filter, wash, and dry in an oven at 50-80°C to obtain modified carbon fiber;

[0038] Carbon paper base preparation method:

[0039] The short-cut aramid fiber is added to 5-15 ml of polyethylene oxide and 1-3 L of tap water so that the mass fraction of the short-cut aramid fiber reaches 2%-14%, and then the solution is placed in a deflaker for deflaking for 5-15 minutes to completely deflake the short-cut aramid fiber to obtain a short-cut aramid fiber solution; then 1.1-1.5 g of modified carbon fiber with a diameter of 3-5 mm and 0.1-0.2 g of polyvinyl alcohol fiber with a diameter of 3-10 mm are added to fully mix the modified carbon fiber, polyvinyl alcohol fiber and the short-cut aramid fiber solution to obtain a slurry, and then the suspension of the slurry is poured into a paper sheet former, and the bubbles are homogenized for 1-5 minutes to uniformly disperse the fibers; the water valve is opened to allow the fibers to settle freely on the copper mesh to form a carbon paper base paper wet paper web, and the excess water in the wet paper web is absorbed by absorbent paper, and finally the wet paper web is placed on a flat vulcanizer, and hot pressed for 10-20 minutes under the conditions of 100-250° C. and 0.5-5 MPa to obtain a carbon paper base paper;

[0040] The steps of hot pressing the carbon paper base are:

[0041] 5-15 g of phenolic resin is weighed and added with 50-150 g of anhydrous ethanol to prepare a 5-15% PF impregnation solution, and ultrasonic vibration is performed for 10-30 minutes to fully mix the phenolic resin impregnation solution, and the carbon paper base paper is ultrasonically impregnated in the phenolic resin impregnation solution for 5-20 minutes, and then placed in a blast drying oven at 50-100° C. for 40-80 minutes to pre-cure the phenolic resin at low temperature. After drying, it is hot-pressed using a flat vulcanizer at a hot pressing temperature of 100-200° C., a hot pressing strength of 1-5 MPa, and a hot pressing time of 20-80 minutes to obtain hot-pressed carbon paper.

[0042] The steps of carbonizing the hot pressed carbon paper to obtain the finished carbon paper are as follows:

[0043] The hot pressed carbon paper is placed in a tubular furnace, and high-purity nitrogen is introduced for 80-100 minutes. Then, the temperature is increased to 100-250°C at a heating rate of 3-10°C / min, and then increased to 800-1500°C at a heating rate of 5-15°C / min, and kept warm for 30-80 minutes. After the reaction is completed, the furnace body is cooled to room temperature to obtain a finished carbon paper product.

[0044] Example 2: Preparation method of carbon paper for proton exchange membrane fuel cell

[0045] Specific method of modifying carbon fiber:

[0046] Step 1, select carbon fiber with a length of 4 mm and disperse it into 1 mol / L, stir it and let it stand to remove grease impurities on the surface of the carbon fiber;

[0047] Step 2: Prepare 0.01 mol / L Tis-HCl solution, add a few drops of Tis-HCl solution to the solution in step 1 to adjust the pH value to 8.5, add the solution after pH adjustment to dopamine hydrochloride solution to prepare 2.5 g / L reaction solution, stir the reaction at room temperature, the color of the solution changes from colorless and transparent to light red, then to dark red, and finally to dark black, and the stirring ends; filter, wash, and dry in an oven at 60°C to obtain modified carbon fiber.

[0048] The specific preparation method of carbon paper is as follows:

[0049] The short-cut aramid fiber is added to 10 ml of polyethylene oxide and 2 L of tap water so that the mass fraction of the short-cut aramid fiber reaches 8%, and then the solution is placed in a deflaker for deflaking for 10 minutes to completely deflake the short-cut aramid fiber to obtain a short-cut aramid fiber solution; then 1.35 g of modified carbon fiber with a diameter of 4 mm and 0.15 g of polyvinyl alcohol fiber with a diameter of 6 mm are added to fully mix the modified carbon fiber, polyvinyl alcohol fiber and the short-cut aramid fiber solution to obtain a slurry, and then the suspension of the slurry is poured into a paper sheet former, and the bubbles are homogenized for 3 minutes to uniformly disperse the fibers; the water valve is opened to allow the fibers to settle freely on the copper mesh to form a carbon paper base paper wet paper web, and the excess water in the wet paper web is absorbed by absorbent paper, and finally the wet paper web is placed on a flat vulcanizer, and hot pressed for 15 minutes at 150° C. and 1 MPa to obtain a carbon paper base paper;

[0050] The specific steps of hot pressing the carbon paper base are:

[0051] Weigh 10g of phenolic resin and add 90g of anhydrous ethanol to prepare a 10% PF impregnation solution. Ultrasonic oscillation is performed for 20 minutes to fully mix the phenolic resin impregnation solution. After ultrasonic impregnation of the carbon paper base paper in the phenolic resin impregnation solution for 10 minutes, it is placed in a blast drying oven at 80°C for 60 minutes to pre-cure the phenolic resin at low temperature. After drying, it is hot-pressed using a flat vulcanizer at a hot pressing temperature of 150°C, a hot pressing strength of 3MPa, and a hot pressing time of 60 minutes to obtain hot-pressed carbon paper.

[0052] The specific steps of carbonizing the hot pressed carbon paper to obtain the finished carbon paper are as follows:

[0053] The hot pressed carbon paper was placed in a tubular furnace, purged with high-purity nitrogen for 90 minutes, then heated to 200°C at a heating rate of 5°C / min, then heated to 1100°C at a heating rate of 10°C / min, and kept warm for 60 minutes. After the reaction was completed, the furnace was cooled to room temperature to obtain the finished carbon paper.

[0054] Example 3: Preparation method of carbon paper for proton exchange membrane fuel cell

[0055] Specific method of modifying carbon fiber:

[0056] Step 1, select carbon fiber with a length of 1 mm and disperse it into 0.9 mol / L, stir and let it stand to remove grease impurities on the surface of the carbon fiber;

[0057] Step 2: Prepare 0.005 mol / L Tis-HCl solution (i.e., trimethylaminoethane hydrochloride buffer solution), add a few drops of Tis-HCl solution to the solution in step 1 to adjust the pH value to 9, add the solution after the pH value is adjusted to the dopamine hydrochloride solution to prepare a 3 g / L reaction solution, stir the reaction at room temperature, the color of the solution changes from colorless and transparent to light red, then to dark red, and finally to dark black, and the stirring ends; filter, wash, and dry in an oven at 70°C to obtain modified carbon fiber.

[0058] The specific preparation method of carbon paper is as follows:

[0059] The short-cut aramid fiber is added to 5 ml of polyethylene oxide and 1 L of tap water so that the mass fraction of the short-cut aramid fiber reaches 14%, and then the solution is placed in a deflaker for deflaking for 5 minutes to completely deflake the short-cut aramid fiber to obtain a short-cut aramid fiber solution; then 1.1 g of modified carbon fiber with a diameter of 4 mm and 0.2 g of polyvinyl alcohol fiber with a diameter of 9 mm are added to fully mix the modified carbon fiber, polyvinyl alcohol fiber and the short-cut aramid fiber solution to obtain a slurry, and then the suspension of the slurry is poured into a paper sheet former, and the bubbles are homogenized for 5 minutes to uniformly disperse the fibers; the water valve is opened to allow the fibers to settle freely on the copper mesh to form a carbon paper base paper wet paper web, and the excess water in the wet paper web is absorbed by absorbent paper, and finally the wet paper web is placed on a flat vulcanizer, and hot pressed for 20 minutes at 100° C. and 5 MPa to obtain a carbon paper base paper;

[0060] The specific steps of hot pressing the carbon paper base are:

[0061] Weigh 15g of phenolic resin and add 80g of anhydrous ethanol to prepare a 10% PF impregnation solution. Ultrasonic vibration is performed for 30 minutes to fully mix the phenolic resin impregnation solution. After ultrasonic impregnation of carbon paper base paper in the phenolic resin impregnation solution for 20 minutes, it is placed in a blast drying oven at 80°C and dried for 80 minutes to pre-cure the phenolic resin at low temperature. After drying, it is hot-pressed using a flat vulcanizer at a hot pressing temperature of 100°C, a hot pressing strength of 5MPa, and a hot pressing time of 20 minutes to obtain hot-pressed carbon paper.

[0062] The specific steps of carbonizing the hot pressed carbon paper to obtain the finished carbon paper are as follows:

[0063] The hot pressed carbon paper was placed in a tubular furnace, purged with high-purity nitrogen for 100 minutes, then heated to 250°C at a heating rate of 3°C / min, then heated to 1500°C at a heating rate of 5°C / min, and kept warm for 80 minutes. After the reaction was completed, the furnace was cooled to room temperature to obtain the finished carbon paper.

[0064] Example 4: Preparation method of carbon paper for proton exchange membrane fuel cell

[0065] Specific method of modifying carbon fiber:

[0066] Step 1, select carbon fiber with a length of 15 mm and disperse it into 3 mol / L, stir it and let it stand to remove grease impurities on the surface of the carbon fiber;

[0067] Step 2: Prepare 0.5 mol / L Tis-HCl solution (i.e., trimethylaminoethane hydrochloride buffer solution), add a few drops of Tis-HCl solution to the solution in step 1 to adjust the pH value to 8, add the solution after pH adjustment to dopamine hydrochloride solution to prepare a 2.5 g / L reaction solution, stir the reaction at room temperature, the color of the solution changes from colorless and transparent to light red, then to dark red, and finally to dark black, and the stirring ends; filter, wash, and dry in an oven at 80°C to obtain modified carbon fiber.

[0068] The specific preparation method of carbon paper is as follows:

[0069] The chopped aramid fiber is added to 15 ml of polyethylene oxide and 3 L of tap water to make the mass fraction of the chopped aramid fiber reach 2%, and then the solution is placed in a deflaker for deflaking for 10 minutes to completely deflake the chopped aramid fiber to obtain a chopped aramid fiber solution; 1.5 g of modified carbon fiber with a diameter of 5 mm and 0.1 g of polyvinyl alcohol fiber with a diameter of 3 mm are added to fully mix the modified carbon fiber, polyvinyl alcohol fiber and the chopped aramid fiber solution to obtain a slurry, and then the slurry suspension is poured into a paper sheet former, and the bubbles are homogenized for 1 minute to uniformly disperse the fibers; the water valve is opened to allow the fibers to settle freely on the copper mesh to form a carbon paper base paper wet paper web, and the excess water in the wet paper web is absorbed by absorbent paper, and finally the wet paper web is placed on a flat vulcanizer, and hot pressed for 12 minutes at 250° C. and 0.85 MPa to obtain a carbon paper base paper;

[0070] The specific steps of hot pressing the carbon paper base are:

[0071] Weigh 5g of phenolic resin and add 100g of anhydrous ethanol to prepare 5% PF impregnation solution. Ultrasonic oscillation is performed for 10 minutes to fully mix the phenolic resin impregnation solution. After ultrasonic impregnation of carbon paper base paper in the phenolic resin impregnation solution for 10 minutes, it is placed in a blast drying oven at 100°C for 40 minutes to pre-cure the phenolic resin at low temperature. After drying, it is hot-pressed using a flat vulcanizer at a hot pressing temperature of 150°C, a hot pressing strength of 1MPa, and a hot pressing time of 60 minutes to obtain hot-pressed carbon paper.

[0072] The specific steps of carbonizing the hot pressed carbon paper to obtain the finished carbon paper are as follows:

[0073] The hot pressed carbon paper was placed in a tubular furnace, purged with high-purity nitrogen for 80 minutes, then heated to 150°C at a heating rate of 7°C / min, then heated to 800°C at a heating rate of 15°C / min, and kept warm for 50 minutes. After the reaction was completed, the furnace was cooled to room temperature to obtain the finished carbon paper.

[0074] Example 5: Test results:

[0075] The mechanical properties of hot pressed carbon paper and carbon paper were tested by a universal tensile machine. The tensile speed of hot pressed carbon paper was 10mm / min, and the tensile speed of carbon paper was 2mm / min. Before the test, the samples were cut from five different areas, and the sample size was 60mm×15mm. The final test results were averaged. The bending strength was measured by three-point bending, the span length was kept at 30mm, the descent rate was 0.5mm / min, and five repeated measurements were performed.

[0076] Depend on Figure 1 It can be seen that the surface of the carbon paper in Example 3 is relatively smooth ( Figure 1 a and Figure 1 b), the surface roughness of the carbon paper in Example 4 is higher than that in Example 3 ( Figure 1 e and Figure 1 f), the surface of the carbon paper of Example 5 is uneven ( Figure 1 c and Figure 1 d), this microstructure is conducive to the composite molding of various components and improves the interface bonding strength of the composite material, thereby improving the mechanical properties of carbon paper.

Claims

1. A method for improving the mechanical properties of carbon paper for proton exchange membrane fuel cells, characterized in that: The steps include: Modified carbon fiber method: Step 1, select carbon fiber with a length of 1-15 mm and disperse it into 0.5-3 mol / L NaOH solution, stir and let stand to remove grease impurities on the surface of the carbon fiber; Step 2: Prepare 0.005-0.5 mol / L Tis-HCl solution, add a few drops of Tis-HCl solution to the solution in step 1 to adjust the pH value to 8-9, add the solution after pH adjustment to dopamine hydrochloride solution to prepare 2-3 g / L reaction solution, stir and react at room temperature, the color of the solution changes from colorless and transparent to light red, then to dark red, and finally to dark black, and the stirring ends; filter, wash, and dry in an oven at 50-80°C to obtain modified carbon fiber; Carbon paper preparation method: The short-cut aramid fiber is added to 5-15 ml of polyethylene oxide and 1-3 L of tap water so that the mass fraction of the short-cut aramid fiber reaches 2%-14%, and then the solution is placed in a deagglomerator for deagglomeration for 5-15 minutes to completely deagglomerate the short-cut aramid fiber to obtain a short-cut aramid fiber solution; then 1.1-1.5 g of modified carbon fiber with a diameter of 3-5 mm and 0.1-0.2 g of polyvinyl alcohol fiber with a diameter of 3-10 mm are added to fully mix the modified carbon fiber, polyvinyl alcohol fiber and the short-cut aramid fiber solution to obtain a slurry, and then the suspension of the slurry is poured into a paper sheet former, and the bubbles are homogenized for 1-5 minutes to evenly disperse the fibers; Open the drain valve to allow the fibers to settle freely on the copper mesh to form a wet paper web of carbon paper base paper, use absorbent paper to absorb excess water in the wet paper web, and finally place the wet paper web on a flat vulcanizer and hot press it for 10-20 minutes at 100-250°C and 0.5-5MPa to obtain a carbon paper base paper; then hot press and carbonize the carbon paper base paper to obtain a finished carbon paper.

2. The method for improving the mechanical properties of carbon paper for proton exchange membrane fuel cells according to claim 1, characterized in that: The steps of hot pressing the carbon paper base are: 5-15 g of phenolic resin is weighed and added with 50-150 g of anhydrous ethanol to prepare a 5-15% PF impregnation solution, and ultrasonic vibration is performed for 10-30 minutes to fully mix the phenolic resin impregnation solution, and the carbon paper base paper is ultrasonically impregnated in the phenolic resin impregnation solution for 5-20 minutes, and then placed in a blast drying oven at 50-100° C. for 40-80 minutes to pre-cure the phenolic resin at low temperature. After drying, it is hot-pressed using a flat vulcanizer at a hot pressing temperature of 100-200° C., a hot pressing strength of 1-5 MPa, and a hot pressing time of 20-80 minutes to obtain hot-pressed carbon paper.

3. The method for improving the mechanical properties of carbon paper for proton exchange membrane fuel cells according to claim 2, characterized in that: The steps of carbonizing the hot pressed carbon paper to obtain the finished carbon paper are as follows: The hot pressed carbon paper is placed in a tubular furnace, and high-purity nitrogen is introduced for 80-100 minutes. Then, the temperature is increased to 100-250°C at a heating rate of 3-10°C / min, and then increased to 800-1500°C at a heating rate of 5-15°C / min, and kept warm for 30-80 minutes. After the reaction is completed, the furnace body is cooled to room temperature to obtain a finished carbon paper product.

4. The method for improving the mechanical properties of carbon paper for proton exchange membrane fuel cells according to claim 1, characterized in that: Specific method of modifying carbon fiber: Step 1, select carbon fiber with a length of 4 mm and disperse it into 1 mol / L, stir it and let it stand to remove grease impurities on the surface of the carbon fiber; Step 2: Prepare 0.01 mol / L Tis-HCl solution, add a few drops of Tis-HCl solution to the solution in step 1 to adjust the pH value to 8.5, add the solution after pH adjustment to dopamine hydrochloride solution to prepare 2.5 g / L reaction solution, stir the reaction at room temperature, the color of the solution changes from colorless and transparent to light red, then to dark red, and finally to dark black, and the stirring ends; filter, wash, and dry in an oven at 60°C to obtain modified carbon fiber.

5. The method for improving the mechanical properties of carbon paper for proton exchange membrane fuel cells according to claim 4, characterized in that: The specific preparation method of carbon paper is as follows: The short-cut aramid fiber is added to 10 ml of polyethylene oxide and 2 L of tap water so that the mass fraction of the short-cut aramid fiber reaches 8%, and then the solution is placed in a deflaker for deflaking for 10 minutes to completely deflake the short-cut aramid fiber to obtain a short-cut aramid fiber solution; then 1.35 g of modified carbon fiber with a diameter of 4 mm and 0.15 g of polyvinyl alcohol fiber with a diameter of 6 mm are added, and the modified carbon fiber, polyvinyl alcohol fiber and short-cut aramid fiber solution are fully mixed to obtain a slurry, and then the suspension of the slurry is poured into a paper sheet former, and the bubbles are homogenized for 3 minutes to evenly disperse the fibers; Open the drain valve to allow the fibers to settle freely on the copper mesh to form a wet paper web of carbon paper base paper. Use absorbent paper to absorb excess water in the wet paper web. Finally, place the wet paper web on a flat vulcanizer and hot press it at 150°C and 1MPa for 15 minutes to obtain a carbon paper base paper. Then, hot press and carbonize the carbon paper base paper to obtain a finished carbon paper.

6. The method for improving the mechanical properties of carbon paper for proton exchange membrane fuel cells according to claim 2, characterized in that: The specific steps of hot pressing the carbon paper base paper are: Weigh 10g of phenolic resin and add 90g of anhydrous ethanol to prepare a 10% PF impregnation solution. Ultrasonic oscillation is performed for 20 minutes to fully mix the phenolic resin impregnation solution. After ultrasonic impregnation of the carbon paper base paper in the phenolic resin impregnation solution for 10 minutes, it is placed in a blast drying oven at 80°C for 60 minutes to pre-cure the phenolic resin at low temperature. After drying, it is hot-pressed using a flat vulcanizer at a hot pressing temperature of 150°C, a hot pressing strength of 3MPa, and a hot pressing time of 60 minutes to obtain hot-pressed carbon paper.

7. The method for improving the mechanical properties of carbon paper for proton exchange membrane fuel cells according to claim 3, characterized in that: The specific steps of carbonizing the hot pressed carbon paper to obtain the finished carbon paper are as follows: The hot pressed carbon paper was placed in a tubular furnace, purged with high-purity nitrogen for 90 minutes, then heated to 200°C at a heating rate of 5°C / min, then heated to 1100°C at a heating rate of 10°C / min, and kept warm for 60 minutes. After the reaction was completed, the furnace was cooled to room temperature to obtain the finished carbon paper.

Citation Information

Patent Citations

  • Preparation method for improving mechanical strength of carbon paper for proton exchange membrane fuel cell

    CN117127434A

  • Method for preparing carbon paper by dipping modified carbon fiber and aramid fiber synergistic resin

    CN118498109A

Cited By

  • Method for improving mechanical strength of carbon fiber paper for proton exchange membrane fuel cell

    CN119994081A